TO TRANSLANGUAGE OR NOT TO TRANSLANGUAGE? THE MULTILINGUAL PRACTICE IN AN INDONESIAN EFL CLASSROOM - Rasman, Rasman (Universitas Pendidikan Indonesia, 2018)
Translanguaging, the use of learners’ full linguistic repertoire in language learning, has recently been theorized as an effective pedagogical practice because it creates more learning opportunities for multilinguals. Despite the growing number of research on this topic, less attention has been paid on the actual use of translanguaging in the classroom. This study aims to fill this gap by investigating translanguaging practice in an EFL classroom in Indonesia where learners used their full repertoire (English, Indonesian, Javanese) to negotiate meaning in learner-learner interactions. Specifically, this research attempts to find out both the effectiveness and the challenges of applying translanguaging to promote learning. The data were collected from the video-recording of naturally-occuring interactions among junior high school students (14-15 years old) in an EFL classroom in Yogyakarta, Indonesia. The data were analyzed using discourse analysis technique and perceived using ecological approach to explain the dialectical relationship between local interaction and the wider socio-political context. The findings show that translanguaging could help learners to develop their multilingual competencies (including the English language). However, the different socio-politically constructed status of English, Indonesian, and Javanese is still prevalent among students and thus, it inhibits them from maximizing their full repertoire when learning English. Further pedagogical implications related to the translanguaging practice for teachers are also suggested in this article.